English Teachers’ Perception toward Milealab (Virtual Reality) as Teaching Media for English Subject in SMPN 3 Solok Selatan - Hafizhah, Rifka; Hilmi, Lafziatul (Universitas Negeri Padang, 2024)
The aim of this study is to analyze teachers' viewpoints regarding the utilization of virtual reality technology as an instructional tool in the context of learning. This study utilized qualitative research methodologies. Four English teachers from SMPN 3 Solok Selatan participated in this study. The data were collected through an interview after the participants tried out the MILEALAB-based materials. This study used Fred Davis's Technology Acceptance Model (TAM) theory (1996) as the theoretical framework. The data analysis in this study involved the examination of four indicators, specifically perceived usefulness, perceived ease of use, attitude to use, and intention to use. The researcher chose to employ Miles and Huberman's flow model in order to analyze the data obtained from the interview. The result showed that many viewpoints existed about virtual reality equipment. Thus, nearly all teachers approve of the utilization of virtual reality in educational settings. According to teachers, the use of virtual reality has been found to enhance English language proficiency as well as increase interest and enthusiasm among individuals who participate in English language learning activities. Also, certain teachers share the viewpoint that improvements should be made to virtual reality course material.